Numerical Model Scenario Analysis of Stilling Basin: A Case Study of Tanahu Hydropower Project (140 MW) - Khadka, Posaraj; Rai, Suman (International Journal on Engineering Technology, 2023)
The difficulty of experimental methods to modify the complex model motivated the researchers to explore alternative solutions. Tanahu Hydropower Project is a storage-type hydropower project. It has an installed capacity of 140 MW and 140 m high concrete dam along with chute-type stilling basin followed by a complex topography. Computational fluid dynamic (CFD) model is a numerical approximation of partial differential equations. It has been widely used to simulate the fluid flow. In this study, a fluid flow is simulated through the stilling basin using the numerical model for different return period floods. The model’s predictions for flow parameters are validated with the results taken from the 1:60 scaled physical models for the same project. The results regarding the flow velocities and water surface level are within 30% and 1.92 m accuracy respectively. The validated model is run for the three modification cases: i) by opening only two of the three spillway gates, ii) by decreasing the depth of the stilling basin, and iii) by decreasing the length of the basin, aiming to recommend the best alternative solution for the effective dissipation of the high kinetic energy of flow from the 140 m high dam. The results reveal that the base case model is the best solution compared to these three modified cases to pass the flood effectively. This study concludes that the CFD model is the effective alternative tool to analyze the fluid flow problems even in the complex geometry and is recommended to use for the design and modification processes.